2022
DOI: 10.1186/s12913-022-07825-6
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transfusion consent and blood delivering pattern improve the management of blood bank in China

Abstract: Background The aim of this study was to improve the blood transfusion treatment consent accuracy, simplify the verification process, prolong the temperature control time before the blood transfusion, and save the blood transportation labor cost. Methods We designed the blood transfusion consent electronic signing process, which can generate personalized the text content and can automatically check the filling accuracy. The signal can be transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Part of this mandate is to help equip hospitals with the appropriate tools to deliver efficient care and meet clinical demands; in a post-pandemic era with significant waiting lists for elective surgery not just in the UK but globally, it is vital that we truly streamline processes so we can meet these demands. As studies have shown digital consent to be faster than paper consent, as well as improving accuracy and reducing mislaid forms [ 10 , 20 ], digital consent appears to be a useful tool in achieving these targets. To achieve patient-centred care, it is vital that technological innovations are appraised before implementation and consider patient experience as an essential part of the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this mandate is to help equip hospitals with the appropriate tools to deliver efficient care and meet clinical demands; in a post-pandemic era with significant waiting lists for elective surgery not just in the UK but globally, it is vital that we truly streamline processes so we can meet these demands. As studies have shown digital consent to be faster than paper consent, as well as improving accuracy and reducing mislaid forms [ 10 , 20 ], digital consent appears to be a useful tool in achieving these targets. To achieve patient-centred care, it is vital that technological innovations are appraised before implementation and consider patient experience as an essential part of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Use of electronic resources in surgical consent has been shown to improve patient’s knowledge of the procedure [ 18 ]. Digital consent has been shown to be equivalent to paper consenting in the time taken to consent [ 19 ], and may even be faster [ 20 , 21 ]. In 2020, a systematic review of the use of digital consent in research concluded that in comparison to paper forms, digital consent has the potential to improve the informed consent process overall [ 22 ].…”
Section: Introductionmentioning
confidence: 99%